Loop Electrosurgical Excisional Procedure (LEEP) Done for Discrepancy: Does the Time from HGSIL Affect Pathologic Grade of CIN in LEEP Specimen? - Sue L. Moreni; Caroline M. Mitchell; Rochelle L. Garcia; Linda O. Eckert (Hindawi Limited, 2010)
Objective. When pathologic discrepancy arises between high-grade cytology on Papanicolaou (Pap) smear and low-grade histology on cervical biopsy, Loop Electrosurgical Excisional Procedure (LEEP) is one management alternative. Our objective was to determine whether the time from initial HGSIL Pap to LEEP affects the pathologic grade of the LEEP specimen. Study Design. We performed a retrospective case-control study identifying LEEPs performed for discrepancy over a 10-year period (1997-2007). 121 subjects were separated into two groups based on LEEP pathology (≤CIN 1 and CIN 2,3) and compared using χ2. Results. Of the 121 LEEP specimens, 67 (55.4%) had CIN 2,3. CIN 2,3 was more often discovered when LEEP was performed within 3 months of the HGSIL Pap smear versus after 5 months (55.2% versus 16.4%, P=.096). Conclusion. Women undergoing LEEP for discrepancy >5 months from their HGSIL Pap demonstrated a trend toward less CIN 2,3 on LEEP pathology.